Methodology for the evaluation of the urban quality of life (2010)
This work exposes theoretical-conceptual aspects and the preliminary results of the urban quality of life model (CVU). It considers the interaction between the basic services, the infrastructure and environmental aspects, the influenced area, and users’ opinion/ perception. Maps were created that tend to express geographically and to define the basic needs related to the urban and infrastructure services. Tendencies are also shown in terms of quality of life, in the function of different urban aspects and their integration and consolidation. Some methodological and operative considerations are carried out which are experienced in the application of the model.